Building Animals Cattle Collective Farming Systems As An Alternative In Anticipation Of Impact Global Warming (Case In Taruna Tani Cocoa Farmers In East Kolaka) - Salam, Idrus; Nafiu, La Ode (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
This study titled build cattle farming systems collectively as an alternative to mitigate the effects of global warming (the case of the cadets peasant farmers in East Kolaka), conducted in June- the month of September 2015, by choosing two districts, namely, District Lambandia and DistrictLalolae, East Kolaka Regency, Southeast Sulawesi Province, Indonesia. The location determination is done by purposive, while sampling done by accidental(convenience sampling) as many as 80 young cadets peasants in each district that's selected. Datawere analyzed using qualitative descriptive. Research results show that the impact of global warming affect or result of a very broad andaffects the lives of cocoa farmers in East Kolaka. This forced farmers to find alternatives to continueto generate revenue one is the development of beef cattle in groups plan administered by thecadets peasants. Taruna farmer has a potential which is very encouraging when viewed from age, educationand experience in farming. However, separately skills to manage the business of cattle still requireintensive counseling. Meanwhile, regarding the opinion / feedback regarding the diversification offarm cattle with cocoa, they generally agree, with the exception of the use of capital still needsupport from the government. It is recommended to government still gives good relief of beef cattlefarming technology and capital support.Keywords: Diversification, Cattle, Cocoa, Cadets Young Farmer, Heating Global.